[Rezension von: Sokoloff, Michael, A dictionary of Jewish Babylonian Aramaic of the Talmudic and Geonic periods] - Beyer, Klaus (Journal of Semitic studies, 2005)
A Dictionary of Jewish Babylonian Aramaic of the Talmudic and Geonic Periods Michael Sokoloff , (Dictionaries of Talmud, Midrash and Targum III and Publications of The Comprehensive Aramaic Lexicon Project). Bar Ilan University Press, Ramat-Gan and The Johns Hopkins University Press, Baltimore 2002. 1582. Price: $160.00 . ISBN: 965-226-260-9